Development of media imperialism in sports and effect of colonialization on Olympic wrestling - Tibor, D.; Barna, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Opposing the practice of the previous centuries, the present day financial and political groups of interests reach their aims not by means of military technique, but via media. The economic, political and cultural capital piled up by the media empires is the result of a kind of modern colonialization. As a consequence of this kind of colonialization, certain nations and social groups lose their previous identity and become defenceless. Sport cannot be an exception from this either, and it is forced to continuously transform/change in favour of increasing Olympic profit. The negative trends having formed during the past decade in the content values of wrestling is continuing. Methods The followings were applied during 1665 bouts (Olympics, World Championships: WCh`85, Atlanta `96, Athen `04, WCh. `05, WCh ` 07, Beijing `08) Direct recorded information from the minutes of the bouts • number of bouts • duration of bouts • number of falls • number of technical points Indirect observation methods • simple attack • complex attack • attempted attack and completed attacks are registered on a special survey sheet Results 1. As a result of the changing rules of the past years, wrestlers have minimised their actions initiated from standing, have decreased the number of their complex, but spectacular actions, have set themselves for holds worth one or two points. The number of falls and technical falls dramatically decreased in the past years, so - although suitable to TV broadcasting - wrestling has gradually lost its spectacle and spirit. 2. The number of technical points for a time unit decreased, which unambiguously means the devaluation of the contextual value of wrestling, although the length of the bouts shows a tendency to before changes 1985. Discussion • Spectacular throws executed from standing and falls should be valued in a way, that it should mean end of the bout. • The first action should have a double value and of decisive importance in case of a tie.